Contracting for Delivering Health - Loevinsohn, Benjamin (World Bank, Washington, DC, 2012)
Substantial improvement in the delivery of health services will be necessary to achieve the health-related Millennium Development Goals (MDGs). A review of developing country experience with contracting for health service delivery was undertaken to examine its effectiveness, determine the extent to which the posited difficulties actually occur in practice, and make recommendations regarding future efforts in contracting. The focus of the review was instances in developing countries of governments contracting with non-state providers (NSPs) to deliver primary health care services including nutrition (but excluding hospital care or ancillary services such as drug procurement and distribution). Based on the success thus far, health services' contracting should be significantly expanded in developing countries as a way of helping achieve the MDGs, and increasing accountability. While the evidence for contracting is reasonably good, future efforts should still include rigorous evaluations to obtain more robust estimates of the effects under various conditions and address unresolved issues, such as the effectiveness of performance bonuses, and means for improving contract management.